Improved Quality Absorber Layer of I–III–VI2 Compound Semiconductors: Purification Process Revisited. Issue 10 (14th August 2019) - Sharma, Shailesh Narain; Chawla, Parul; Nutan, Gautam V.; Vijayan, Narayanasamy; Singh, Vidyanand; Srivastava, Avinash Kumar; Vashishtha, Parth
Abstract : Copper–indium–gallium–selenide (CIGSe) is one of the most stable and promising materials for photovoltaic applications. Herein, the synthesis process of CIGSe nanocrystals using a tri‐octyl phosphine/tri‐octyl phosphine oxide (TOP/TOPO) method that has the shortest duration (≈45 min), as compared to other nonvacuum‐based approaches, is reported. Most solution‐based approaches are Se‐deficient and therefore utilize a post‐selenization process such as rapid thermal processing (RTP) at a high temperature to form CIGSe. RTP creates voids and defects in CIGSe films. The synthesis process does not need post‐selenization processes as it is not Se‐deficient. It also includes the purification and processing techniques of these CIGSe nanocrystals for a variety of printing and coating techniques. The purification process offers improved charge transport between CIGSe nanocrystals for the realization of efficient photovoltaic device without resorting to soda lime glass (SLG), post‐deposition thermal selenization, or harsh chemical treatments. In addition, this process avoids the incidence of contamination, such as with copper selenide and amorphous carbon, which is a common issue in solution‐based techniques, and thus provides high‐purity CIGSe ink. To identify the effects of the purification process, the synthesized ink is qualitatively and quantitatively characterized before and after each purification step. Abstract : Herein, a chemical synthesis route of Se‐rich CIGSe nanocrystals is highlighted to avoid high‐temperature post‐treatment, which creates voids and defects in thin films. Charge transport properties of nanocrystals depend on the surface and the amount of ligands. More importantly, an optimized washing process is the key to fabricate high‐quality CIGSe films for photovoltaics.